Suspended silt and salinity tolerances of the first zoeal stage of the fiddler crab Uca annulipes (Decapoda: Brachyura) and why marine connectivity is essential to the survival of the species. Issue 2 (19th August 2016) - Peer, N; Miranda, NAF; Perissinotto, R
Abstract : Fiddler crabs ( Uca spp.) undergo the zoeal stage of development in open-ocean waters, where they experience stable salinity levels, low turbidity and reduced predation. The St Lucia estuarine system has undergone many geomorphological changes, both natural and anthropogenic, and the estuary mouth has been closed since the early 2000s. Despite recent attempts to improve marine connectivity, it remains limited, occurring primarily on the flood tide through channels connected to the adjacent Mfolozi River. Larval export from the St Lucia Estuary is therefore almost non-existent. A laboratory study was undertaken to examine the silt and salinity tolerance of Uca annulipes first stage zoeae, to investigate whether survival in the closed-estuary conditions would be possible. Salinity tolerance was narrow, with zoeae displaying 100% mortality at salinities <20 and >35 after five days. Zoeae were widely tolerant to silt loading and did not display a significant decrease in survival over a range of 0–1 000 NTU. A limited salinity tolerance is in accordance with the life-history strategy of fiddler crabs, and a high tolerance to turbid waters can be advantageous to small-bodied merozooplankton. Given the stenohaline nature of the zoeae, marine connectivity is therefore essential for the persistence of U. annulipes in this estuarine habitat.